ANALISIS PENERAPAN AKUNTANSI KEBERLANJUTAN DALAM MENINGKATKAN NILAI PERUSAHAAN - Rezki Zurriah; Isna Ardila (UNIVERSITAS DHARMAWANGSA, 2026)
This study aims to analyze the implementation of sustainable accounting in increasing the value of the Company at PT Bank Sumut from 2020 to 2024. This study uses a descriptive qualitative approach with data sources in the form of annual reports, sustainability reports obtained from PT Bank Sumut. The analysis is carried out based on the Global Reporting Initiative (GRI) standards and the Price to Book Value (PBV) approach for firm value. Sustainable accounting is an accounting concept that integrates economic, social and environmental aspects in the Company's operational activities and reporting. The results of this study indicate that the firm value of PT Bank Sumut from 2020 to 2024 shows that the firm value using the PBV approach has increased from year to year. Meanwhile, the implementation of sustainable accounting at PT Bank Sumut has been proven to have a positive impact on increasing company value. The implementation of sustainable accounting at PT Bank Sumut has an important role in supporting the increase in firm value both from financial and non-financial aspects. Keyword: Sustainable Accounting, Firm Value